ORAL TRADITION OF DEWI KRESNA DANCE DRAMA PERFORMANCE IN KERAMBITAN TABANAN - BALI: A STUDY VIEWED FROM FUNCTION AND VALUE PERSPECTIVE - I Nengah Astawa; I Nyoman Suparsa; Ida Bagus Nyoman Mantra; Ni Luh Sukanadi (Unmas Press, 2020)
The purpose of this study is to describe functions and values ​​of Dewi Kresna Dance-Drama Performance in Kerambitan Tabanan. The underlying theories used as the basis of this research are the theories of structuralism and hermeneutics. The data of the research was obtained through conducting field observation, interviewing some source persons, research libraries and recording the performance on the spot. The result of the recording was transcripted and translated literally and idiomatically. Then it was analyzed descriptively using argumentative techniques. The result of the findings is that the plot of the story is made up with two main acts with nine types of conventional scenes. The characters involved in the performance were categorized into stock characters, conventional formulaic ones who are always present in every traditional performance in Bali and also central characters. Why Dewi Kresna is used here, not Calonarang as commonly used in the other parts of Bali is due to the factors of feeling, esthetics and the society's belief in Kerambitan. They avoid using